282 PREDICTORS OF MYOCARDIAL FUNCTION AFTER PATENT DUCTUS ARTERIOSUS LIGATION AS ASSESSED BY THE MYOCARDIAL PERFORMANCE INDEX. (1st January 2006) - Adie, M.; Noori, S.; Friedlich, P.; Payan, A.; Seri, I.
Abstract : Background: Several studies have reported a deterioration in cardiovascular status following surgical ligation of patent ductus arteriosus (PDA). Our group has previously reported a worsening of myocardial function as assessed by the myocardial performance index (MPI). MPI, also known as the Tei index, is a Doppler-derived measure of global myocardial function. It is inversely related to myocardial function. Objective: To identify the clinical and echocardiographic predictors of MPI in a group of preterm infants undergoing surgical PDA closure. Methods: Preterm infants who had a PDA ligation during the period of March 2004 to September 2005 comprised our study population. Data were collected both retrospectively ( n = 11) and prospectively ( n = 8). Cardiac function was assessed before and after PDA ligation using a Philips SONOS 5500 ultrasound machine. Relevant variables including birth weight, gestational age, postmenstrual age (PMA), age at ligation, dopamine dose, PDA size, and ventilatory mean airway pressure (MAP) were collected. Univariate and multivariate linear regression models were used to investigate the relationship between MPI and clinical or echocardiographic variables. Results: Complete sets of data were available in 19 preterm infants (GA 25.7 ± 2 wks, Bwt 788 ± 257 g, PMA 28.6 ± 2.7 wks) who underwent PDA ligation on day of life 20 ± 12. Consistent with our previously reported findings, MPI increased from 0.26 ± 0.11 to 0.55 ± 0.21 following the PDA ligation ( p < .001). In this patient population, after adjusting for the need of MAP ≥ 9 cmH2O and the requirement of dopamine ≥ 10 μg/kg/min, PDA size was significantly associated with an increase in MPI values (R 2 = .31, p = .03). Conclusion: Following PDA ligation, the size of the PDA predicts the deterioration in cardiac function as measured by the MPI.